2019
DOI: 10.1016/j.metop.2019.100017
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 is inversely associated with type 2 diabetes independently of obesity – A SCAPIS pilot study

Abstract: Objectives Galectin-1 is a recently discovered adipokine that increases with obesity and increased energy intake in adipose tissue. Our aim was to assess whether serum galectin-1 is associated with type 2 diabetes (T2D) and other parameters of the metabolic syndrome independently of body mass index (BMI) in a cohort from the general population. Methods In this cross-sectional population-based cohort study from the western part of Sweden, we investigated associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 17 publications
7
25
0
Order By: Relevance
“…The relationship between obesity, type 2 diabetes and declined renal function is well known [ 31 33 ], although the causal pathways are not fully established [ 34 ]. In agreement with earlier epidemiological studies, BMI and related clinical markers of the metabolic syndrome correlated with circulating galectin-1 levels in our study [ 17 , 35 ]. Conversely, we have previously reported that there is an inverse relationship between galectin-1 and type 2 diabetes when adjusting for BMI [ 17 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The relationship between obesity, type 2 diabetes and declined renal function is well known [ 31 33 ], although the causal pathways are not fully established [ 34 ]. In agreement with earlier epidemiological studies, BMI and related clinical markers of the metabolic syndrome correlated with circulating galectin-1 levels in our study [ 17 , 35 ]. Conversely, we have previously reported that there is an inverse relationship between galectin-1 and type 2 diabetes when adjusting for BMI [ 17 ].…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with earlier epidemiological studies, BMI and related clinical markers of the metabolic syndrome correlated with circulating galectin-1 levels in our study [ 17 , 35 ]. Conversely, we have previously reported that there is an inverse relationship between galectin-1 and type 2 diabetes when adjusting for BMI [ 17 ]. A study on pregnant women also reported that participants develop gestational diabetes when the adaptive increase of galectin-1 is impaired during pregnancy [ 36 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Pharmacological inhibition of LGALS1 displayed important anti-obesogenic and anti-adipogenic effects [ 48 , 49 ], strengthening the role of this protein in the development of fat mass and obesity. Otherwise, circulating galectin-1 levels were negatively associated with type 2 diabetes [ 50 , 51 ], indicating that it might be associated with healthy adiposity. PHB is induced during adipocyte differentiation, in response to insulin and PPARγ agonist, and its overexpression in 3T3-L1 fibroblasts was sufficient to induce adipogenesis [ 52 ], but its gene knockdown reduces the expression of adipogenic genes and lipid accumulation and impairs mitochondrial dysfunction [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%